CERTIDÕES DE NASCIMENTO, CASAMENTO E ÓBITO: UM PERCURSO COM BASE EM CORPUS COMPARÁVEL PARA A EXTRAÇÃO DE FRASEOLOGIAS DE DOCUMENTOS OFICIAIS - Eduardo Francisco Ferreira (2024)
ABSTRACT Translation work is not as simple as accessing the source text's vocabulary and replacing it with equivalent terms in the target language. Beyond this naive view, there are other elements that must be considered when transferring communicative elements from one language to another. In this context, the translator, in addition to having advanced linguistic knowledge, needs to be equipped with other factors involved in this process to ensure that the translated text fits appropriately into the target language and achieves the same impact it had in the source language. With technological development and the advancement of research, many interfaces have been created, revealing new fields of study and, consequently, generating the need for terminological products that can assist translators when dealing with specialized texts. In light of this, the objective of this work is to present a path, based on a comparable corpus, for the compilation of a glossary derived from the content of certificates and certified translations of birth, marriage, and death certificates from Brazil and the United States, carried out by sworn Brazilian translators. The theoretical framework is grounded in the principles of Terminology, combined with those of Corpus Linguistics and Translation Studies. Our results indicate the existence of a path that can be drawn at the interface between Terminology and Translation Studies, specifically technical translation, two relatively young fields that, by sharing elements and objectives, can produce a product that meets the translator's needs in overcoming translational challenges. The analyses focused on designing the ideal dictionary entry to assist the translator in locating terms and phraseologies of certificates within the target culture. Keywords: Certificates, Translation, Comparable Corpus, Phraseology.